Metode psikoedukasi dan mind mapping untuk meningkatkan kontrol sosial orangtua pada penggunaan gadget anak - Sabila Anggarawati (Fakultas Psikologi, 2020)
Social control is any process planned or unplanned, which is to investigate, encourage, even force, an individual to comply with prevailing social values. This topic is important to examine when it comes to the use of social gadgets. The lack of social control of the parents in terms of use of gadgets in children will encompass various negative impacts in terms of psychological and physical. Psychoeducation and mind mapping are selected as a method of intervention to improve parental social control in terms of use of gadgets in children. The purpose of this intervention is to improve the social control of parents on the use of child gadgets that are done with the provision of psychoeducation and mind mapping. This research is an experimental research with control group pre-test post-test design. The measuring instrument used is the social control scale. The result of the analysis using paired sample t test with the result (Z = -4,103; p = 0,000 <0,05 = meaning there is significant difference between pretest and posttest score. It can be concluded that psychoeducation and mind mapping increase social control of parent at use of child gadgets.